Foamy dark matter from monodromies - Berges, Jürgen; Chatrchyan, Aleksandr; Jaeckel, Joerg (Journal of cosmology and astroparticle physics, 2019)
We investigate the dynamics of axion-like particle (ALP) dark matter where the field range is enlarged by a monodromy. The monodromy potential allows sufficient production of dark matter also at larger couplings to the Standard Model particles. The potential typically features a number of “wiggles” that lead to a rapid growth of fluctuations. Using classical-statistical field theory simulations we go beyond the linear regime and treat the system in the non-linear and even non-perturbative regime. For sufficiently strong wiggles the initially homogeneous field is completely converted into fluctuations. The fluctuations correspond to dark matter particles with a non-vanishing velocity and we consider the corresponding restrictions from structure formation as well as the effects on today's dark matter density.
Gesehen am 08.11.2019